Evaluation of foot analysis in the presence of dental malocclusion: A systematic review - Sofyanti, Ervina; Alhasyimi, Ananto Ali; Farmasyanti, Cendrawasih Andusyana; Purbiati, Maria; Mardiati, Endah; Narmada, Ida Bagus; Utomo, Haryono; Gio, Prana Ugiana; Marya, Anand (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Previous studies have reported that the imbalance of occlusion, cervical spine, length of the limb, and asymmetric leg length are related to the presence of muscle compensation. These issues influence some strategies in orthodontic diagnosis for developing an updated stomatognathic system over multidisciplinary care issues. Purpose: This study aimed to obtain orthodontic findings and an orthopedic relationship between foot posture/function and dental malocclusion based on cross-sectional studies. Review: Some findings about postural system disequilibrium in static and dynamic foot postural related to occlusal changes have been reported following the mixed dentition phase. From 248 articles, 5 articles were selected and assessed with the Joanna Briggs Institute critical appraisal cross-sectional checklist and analyzed. Conclusions: Although the selected eligible articles demonstrated a low risk of bias in agreement (p > 0.05) among authors, the evaluation of those cross-sectional studies is still limited and requires further longitudinal studies with precise diagnostic parameters. Those parameters for evaluating the relationship between foot posture and malocclusion should encompass both static and dynamic approaches, including those related to mandibular position, tongue posture and function, bad habits, and temporomandibular disorder.